Myocardial contrast echocardiography is superior to other known modalities for assessing myocardial reperfusion after acute myocardial infarction - Greaves, K (Copyright 2003 by Heart, 2003)
Background: Angiographic flow measurements do not define perfusion accurately at a microvascular level, so other techniques which assess flow at a tissue level are to be preferred. Objectives: To compare intravenous myocardial contrast echocardiography (MCE) with other methods of assessing microvascular reperfusion for their ability to predict left ventricular function at one month after acute myocardial infarction. Design: 15 patients underwent primary percutaneous coronary angioplasty for acute myocardial infarction, with restoration of TIMI grade 3 flow. Corrected TIMI frame count (cTFC), myocardial blush grade (MBG), and percentage ST segment resolution at 90 and 180 minutes were recorded. Baseline regional wall motion score index (WMSI) and regional contrast score index (RCSI) were obtained 12–24 hours after the procedure, with a final regional WMSI assessment at one month. Results: Mean (SD) cTFC was 27 (9.4), and ST segment resolution was 69 (22)% at 90 minutes and 77 (20)% at 180 minutes. MBG values were 0 in six patients, 2 in two, and 3 in seven. Baseline regional WMSI, RCSI, and follow up WMSI were 2.7 (0.71), 1.5 (0.71), and 1.6 (0.73), respectively. The correlation coefficient between RCSI and follow up WMSI was 0.82 (p = 0.0012). Peak CK correlated with follow up WMSI (R = 0.80). None of the other reperfusion assessment techniques correlated significantly with follow up WMSI. Multiple regression analysis showed that a perfused hypokinetic or akinetic segment was 50 times more likely to recover function than a non-perfused segment. MCE predicted segmental myocardial recovery with a sensitivity of 88%, a specificity of 74%, and positive and negative predictive values of 83% and 81%, respectively. Conclusions: MCE is currently the best and most accurate measure of reperfusion at a microvascular level and an excellent predictor of left ventricular function at one month following acute myocardial infarction.